2011
DOI: 10.2478/s11696-011-0054-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of carbon in solidified sodium coolant using new ICP-OES methods

Abstract: New methods for the determination of carbon in sodium using laser ablation inductively coupled plasma optical emission spectrometry (LA-ICP-OES) and ICP-OES with pneumatic nebulisation (PN-ICP-OES) were developed. The determination was required for the study of the carbon dioxide reaction with molten sodium at high temperatures (300–600°C). After exposition to CO2, the solidified sodium sample was subjected to direct solid analysis by LA-ICP-OES and to solution analysis. For the determination of carbon in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The heat of combustion (Libing et al, 2021), thermogravimetric parameters (Junfeng et al, 2021), fat contents (Novokshanova et al, 2019;Pauter et al, 2018), crude fiber contents (Oboh, 2006;Slama et al, 2019), ash contents (Hassid et al, 2022;Krishna et al, 2022;Šimonovičová et al, 2021), and contents of trace elements (Ohata et al, 2009;Vaculovič et al, 2011) for 5 kinds of tea were determined. According to the combustion heat, thermogravimetric parameters, fat contents, crude fiber contents, trace element contents and ash contents, the multi-index entropy method, gray pattern recognition and entropy cluster analysis of 5 kinds of tea were performed in Yunnan, China.…”
Section: Methodsmentioning
confidence: 99%
“…The heat of combustion (Libing et al, 2021), thermogravimetric parameters (Junfeng et al, 2021), fat contents (Novokshanova et al, 2019;Pauter et al, 2018), crude fiber contents (Oboh, 2006;Slama et al, 2019), ash contents (Hassid et al, 2022;Krishna et al, 2022;Šimonovičová et al, 2021), and contents of trace elements (Ohata et al, 2009;Vaculovič et al, 2011) for 5 kinds of tea were determined. According to the combustion heat, thermogravimetric parameters, fat contents, crude fiber contents, trace element contents and ash contents, the multi-index entropy method, gray pattern recognition and entropy cluster analysis of 5 kinds of tea were performed in Yunnan, China.…”
Section: Methodsmentioning
confidence: 99%
“…The depth-profile analysis of the exposed solidified sodium provided evidence of the penetration of the chemical reaction into the sodium coolant. 21 The influence of exposition time on corrosion depth for the selected candidate structural materials Inconel A686 and stainless steel 1.4571 in the presence of LiF-NaF molten salt mixture at 680 C has recently been studied by EPMA and laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS), while the concentration of corrosion products in the exposed LiF-NaF mixture was determined by ICP-OES. It was concluded that EPMA makes it possible to obtain quantitative assessment of the corrosion process, and LA-ICP-MS single-line raster profiles can be converted from a signal domain to elemental contents on a semi-quantitative level by using signal normalization to the total sum of signals of isotopes.…”
Section: Introductionmentioning
confidence: 99%